2013
DOI: 10.1128/jvi.01348-13
|View full text |Cite
|
Sign up to set email alerts
|

An Eight-Segment Swine Influenza Virus Harboring H1 and H3 Hemagglutinins Is Attenuated and Protective against H1N1 and H3N2 Subtypes in Pigs

Abstract: Swine influenza virus (SIV) infections continue to cause production losses in the agricultural industry in addition to being a human public health concern. The primary method of controlling SIV is through vaccination. The killed SIV vaccines currently in use must be closely matched to the challenge virus, and their protective efficacy is limited. Live attenuated influenza vaccines (LAIV) provide strong, long-lived cell-mediated and humoral immunity against different influenza virus subtypes with no need for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…Evidence for this was first provided by showing the presence of anti-GFP Abs in mice following immunization with a GFP-expressing sciIAV ΔPB2 (Victor et al, 2012). Furthering this data, when a reporter gene from a sciIAV was replaced by an inactive HA gene from a heterologous IAV, both mice and swine were protected against heterologous influenza virus infections (Masic et al, 2013; Uraki et al, 2013). However, no NAbs were detected against the heterologous strain in mice even though they were detected in swine.…”
Section: Sciiav Applicationsmentioning
confidence: 83%
See 2 more Smart Citations
“…Evidence for this was first provided by showing the presence of anti-GFP Abs in mice following immunization with a GFP-expressing sciIAV ΔPB2 (Victor et al, 2012). Furthering this data, when a reporter gene from a sciIAV was replaced by an inactive HA gene from a heterologous IAV, both mice and swine were protected against heterologous influenza virus infections (Masic et al, 2013; Uraki et al, 2013). However, no NAbs were detected against the heterologous strain in mice even though they were detected in swine.…”
Section: Sciiav Applicationsmentioning
confidence: 83%
“…Moreover ferrets, which have upper respiratory physiology more closely related to humans than mice and can transmit influenza via aerosol droplets, were also protected by sciIAV against infection and transmitting virus (Baker et al, 2013). Vaccination with sciIAV in swine was also shown to be protective and immunogenic (Masic et al, 2013; Pyo and Zhou, 2014). …”
Section: Sciiav Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in nonpregnant mice have demonstrated that a single dose of sciIAV vaccine confers protection against heterosubtypic lethal challenge without any adverse effects. 136 141 Similar safety and efficacy profiles of sciIAV have been replicated in ferret and pig models, 136 , 142 but studies in pregnant animals have not been performed. Compared with the risks associated with live virus vaccination and concerns of efficacy with inactivated vaccines, novel vaccine platforms, such as nanoparticle-based technologies, VLPs and replication-deficient viruses have proven benefits.…”
Section: Application Of Novel Vaccine Platformsmentioning
confidence: 95%
“…Traditionally, pigs have mostly been used for the development of swine influenza virus vaccines, for which several novel approaches are under investigation [ 160 , 161 , 162 ]. Similarly to humans [ 163 ], mice [ 128 ] and ferrets [ 164 , 165 ], seasonal H1N1 vaccination (inactivated or live-attenuated) induced minimal cross-reactive humoral responses, and showed marginal efficacy against a pandemic H1N1 challenge [ 166 ].…”
Section: Evaluation Of Broadly Protective Influenza Vaccines In Anmentioning
confidence: 99%